Optimization method for the three-level logistics of product oil in the context of pipeline marketization - Renfu TU; Hao ZHANG; Yiwei SU; Liyan HUANG; Siliang HUANG; Guangtao FU; Xiaomin ZHANG; Rui QIU; Yongtu LIANG (You-qi chuyun, 2025)
ObjectiveChina’s product oil logistics currently operates under a hierarchical management structure comprising three levels: refinery to oil depot, oil depot to oil depot, and oil depot to filling station. Independent optimization at each level leads to significant deviations from the optimal operational costs for the entire logistics system, indicating potential for improved operational efficiency. Additionally, the market-oriented reform of product oil pipelines further diminishes the effectiveness of traditional optimization methods for the three-level logistics. MethodsThis paper analyzed the structural characteristics of three-level product oil logistics and integrated the market-oriented pricing strategy for pipeline transportation to propose an optimization model aimed at minimizing overall logistics costs. The model accommodated various constraints, including mass conservation at refineries and depots, demand fulfillment at filling stations, pipeline transport capacity limitations, transfer capacity restrictions at depots, and the activation of tiered transport rates. A comprehensive framework for optimizing the three-level logistics was established through this approach. ResultsThe developed model was applied to the three-level logistics system for product oil in a certain region of China. The overall optimization resulted in coordinated transportation plan and route scheme for refinery-oil depot-filling station, effectively addressing the issue of “proximity in the third-level logistics leading to remoteness in the first- and second-level logistics”. Strategies included the “forward movement” of supply depots and the exploration of transfer depots. This application reduced regional oil transportation costs by RMB 17.5 per ton, achieving a 10％ decrease. ConclusionThe established optimization framework and model demonstrate significant versatility, applicable to three-level logistics systems of various scales and structures. They offer valuable guidance for the management and operation of product oil sales companies, with substantial potential for economic benefits and improved overall logistics efficiency.